2016
DOI: 10.1136/bmjopen-2016-011647
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and explanations of mental ill health in a group of devout Christians from the ethnic majority population in secular Sweden: a qualitative study

Abstract: ObjectiveTo explore existential meaning-making in an ethnic-majority subgroup with mental ill health and to increase knowledge about the importance of gaining access to such information in mental healthcare.DesignQualitative study using in-depth interviews and systematic text condensation analysis.Participants17 devote Christians with an ethnic-Swedish background, 12 women and 5 men, 30–73 years old, from different congregations across Sweden, having sought medical care for mental ill health of any kind.Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Existential sense making in here refers to all sorts of expressions and to how health is interpreted, such as traditional and religious expressions as well as other circumstantial expressions (Lilja et al . ). Health is conceptualised as a feeling that can control every mechanism of the human body, including their physical, psychological, social, emotional and spiritual features, and this aligns with the model as defined by the World Health Organization ().…”
Section: Discussionmentioning
confidence: 97%
“…Existential sense making in here refers to all sorts of expressions and to how health is interpreted, such as traditional and religious expressions as well as other circumstantial expressions (Lilja et al . ). Health is conceptualised as a feeling that can control every mechanism of the human body, including their physical, psychological, social, emotional and spiritual features, and this aligns with the model as defined by the World Health Organization ().…”
Section: Discussionmentioning
confidence: 97%
“…Total GHQ-20 scores were lower in the Uygur and Kazak minorities than in the majority Han ethnic group, possibly due to beliefs and religious activities that can lower the risk of mental health problems [ 47 ] and often give people hope and support when they are sick or in trouble [ 48 ]. Religious beliefs have also been shown to influence behavior and health in both simple and complex ways [ 49 ], and have been shown to have protective effects against depression and psychosis [ 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of Spiritual practices helped participants to cope with their mental health problems with prayer having particular significance (Al-Solaim and Loewenthal, 2011;Eltaiba and Harries, 2015). People's Spiritual relationship, whether with God, a spiritual figure or a higher spiritual power was often significant for participants, being described as central to their faith or the most important relationship of their lives with crucial importance for coping during times of illness (Lilja, et al, 2016;Hanevik et al, 2017;Oxhandler et al, 2018). Heffernan et al (2016) found that the role of a genuine reciprocal relationship with a spiritual figure was so essential that it influenced many other aspects of people's experiences and that recovery was impeded when the relationship was disrupted within hospital settings.…”
Section: Copingmentioning
confidence: 99%